2021
DOI: 10.3390/toxins13090645
|View full text |Cite
|
Sign up to set email alerts
|

ExlA Pore-Forming Toxin: Localization at the Bacterial Membrane, Regulation of Secretion by Cyclic-Di-GMP, and Detection In Vivo

Abstract: ExlA is a highly virulent pore-forming toxin that has been recently discovered in outlier strains from Pseudomonas aeruginosa. ExlA is part of a two-partner secretion system, in which ExlA is the secreted passenger protein and ExlB the transporter embedded in the bacterial outer membrane. In previous work, we observed that ExlA toxicity in a host cell was contact-dependent. Here, we show that ExlA accumulates at specific points of the outer membrane, is likely entrapped within ExlB pore, and is pointing outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The current hypothesis is thus that the active form of the toxin is that anchored by ExlB in the outer membrane, rather than the secreted protein (Figure 1C). Proteinase digestion experiments showed that a part of ExlA is pointing out of the bacterial membrane and further supports a model in which ExlA, entrapped in the outer membrane, could interact with a potential receptor located at the host cell surface (Deruelle et al, 2021). This secretion model is analogous to that described for contact-dependent inhibition (CDI) toxins, belonging to the TPS family, for which passenger translocation across the outer membrane stalls at mid-length in the TPS transporter and resumes upon interaction with a target receptor (Ruhe et al, 2018).…”
Section: Exla Secretionsupporting
confidence: 68%
See 4 more Smart Citations
“…The current hypothesis is thus that the active form of the toxin is that anchored by ExlB in the outer membrane, rather than the secreted protein (Figure 1C). Proteinase digestion experiments showed that a part of ExlA is pointing out of the bacterial membrane and further supports a model in which ExlA, entrapped in the outer membrane, could interact with a potential receptor located at the host cell surface (Deruelle et al, 2021). This secretion model is analogous to that described for contact-dependent inhibition (CDI) toxins, belonging to the TPS family, for which passenger translocation across the outer membrane stalls at mid-length in the TPS transporter and resumes upon interaction with a target receptor (Ruhe et al, 2018).…”
Section: Exla Secretionsupporting
confidence: 68%
“…Both ExlA and ExlB are predicted to be secreted into the periplasm by the sec pathway. ExlA accumulates at the outer membrane as shown by cellular fractionation experiments ( Deruelle et al., 2021 ) ( Figure 1C ). Microscopy immunolocalization identified ExlA spots at the bacterial periphery.…”
Section: Exla Secretionmentioning
confidence: 76%
See 3 more Smart Citations